IMPLEMENTASI MANAJEMEN KURIKULUM 2013 - Sujana, Dana; Anis Zohriyah,; Anis Fauzi, (Journal of Innovation Research and Knowledge, 2022)
Th purpos of this study was to describ th implementation of th curriculum 2013 and to find out th supporting and inhibiting factors for implementing th curriculum. This research is a typ of qualitativ research with a field study approach. Th primary research data ar in th form of observations and interviews whil secondary data comes from various sources of writing/literatur in th form of books, journals, magazines related to research problems. Th data analysis used is descriptiv data analysis becaus it aims to fully describ th phenomenon of th problem being studied. Conclusions ar drawn after verifying th data found in th research field. then checking th validity of th data is don by using tringulation technique. Th results of th study revealed that th implementation of th curriculum 2013 was adjusted to th vision and mission of th Islamic boarding school and carried out with th stages of planning, implementing, evaluating and developing curriculum. Th supporting factors ar support from th leadership of th pesantren and th ustadzah, most of th teachers ar graduates and alumni at this boarding school, adequat facilities and infrastructure. Whil th inhibiting factors includ th lack of teacher motivation, monotonous learning, th dominanc of th lectur method, som teachers ar still in college